Computer of the future: DNA instead of silicon? - Lorkowski S; Cullen P (Journal of Laboratory Medicine / Laboratoriums Medizin, 2000)
Computers based on the use of nucleic acids as storage media and molecular techniques for computations are no longer science fiction. Compared with standard computers based on silicon chips, which work with binary logic (on and off as possible decisions), DNA computers are parallel processing machines, which can use four possible decisions depending on the four compounds of nucleic acids (G, A, T, and C). This ability of DNA computers make it possible to solve mathematical problems which cannot be solved using conventional computers. Mathematical puzzles with exponentially growing numbers of solutions depending on the linear increase in variables can be solved by DNA computers, because the computation time of a parallel computer compared with a binary computer increases as a linear function of the number of variables. There are still a lot of technical problems to be solved and the procedures needed for computable operations of a DNA computer are labour- and time-intensive. Nevertheless, DNA computers represent the first step towards computers with the possibility of computing directly with molecules.